2019
DOI: 10.3389/fpsyt.2018.00768
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Machine Learning Approaches for Predicting Antidepressant Treatment Response Using Electroencephalography (EEG) and Clinical Data

Abstract: Background: Individuals with major depressive disorder (MDD) vary in their response to antidepressants. However, identifying objective biomarkers, prior to or early in the course of treatment that can predict antidepressant efficacy, remains a challenge.Methods: Individuals with MDD participated in a 12-week antidepressant pharmacotherapy trial. Electroencephalographic (EEG) data was collected before and 1 week post-treatment initiation in 51 patients. Response status at week 12 was established with the Montgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 108 publications
(116 reference statements)
2
74
0
Order By: Relevance
“…Moreover, the alpha rhythm is prominent (e.g., visible in raw EEG traces) and reliably quantified by different research groups using different methodologies (e.g., Barry & De Blasio, 2018;Labounek et al, 2018;Schmidt et al, 2017;Shackman et al, 2010;Sockeel, Schwartz, Pélégrini-issac, & Benali, 2016;Tenke et al, 2017). Importantly, greater posterior alpha oscillations at rest predicted a favorable clinical outcome for individuals diagnosed with MDD (Baskaran et al, 2017;Bruder et al, 2008;Jaworska, de la Salle, Ibrahim, Blier, & Knott, 2019;Kandilarova et al, 2017;Knott et al, 1996;Tenke et al, 2011;Ulrich, Renfordt, Zeller, & Frick, 1984;Ulrich, Renfordt, & Frick, 1986; although see Arns et al, 2016, andKnott, Mahoney, Kennedy, &Evans, 2000, for unsuccessful attempts to replicate these findings). To some degree, these reports differed in methodology, including EEG montage (density, locations) and reference, preprocessing steps, and a priori selection of frequency bins.…”
Section: Research Findings On Posterior Alphaband Activity As a Canmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the alpha rhythm is prominent (e.g., visible in raw EEG traces) and reliably quantified by different research groups using different methodologies (e.g., Barry & De Blasio, 2018;Labounek et al, 2018;Schmidt et al, 2017;Shackman et al, 2010;Sockeel, Schwartz, Pélégrini-issac, & Benali, 2016;Tenke et al, 2017). Importantly, greater posterior alpha oscillations at rest predicted a favorable clinical outcome for individuals diagnosed with MDD (Baskaran et al, 2017;Bruder et al, 2008;Jaworska, de la Salle, Ibrahim, Blier, & Knott, 2019;Kandilarova et al, 2017;Knott et al, 1996;Tenke et al, 2011;Ulrich, Renfordt, Zeller, & Frick, 1984;Ulrich, Renfordt, & Frick, 1986; although see Arns et al, 2016, andKnott, Mahoney, Kennedy, &Evans, 2000, for unsuccessful attempts to replicate these findings). To some degree, these reports differed in methodology, including EEG montage (density, locations) and reference, preprocessing steps, and a priori selection of frequency bins.…”
Section: Research Findings On Posterior Alphaband Activity As a Canmentioning
confidence: 99%
“…This is important for clinical utility, as specific brain regions likely have differential relatedness to psychiatric outcomes, and EEG reference choices will vary from clinic to clinic. There are myriad techniques and tools available to accomplish these aims, yet it remains to be seen which specific techniques are best for clinical prediction (Bridwell et al, 2018;Delorme et al, 2012;Jaworska et al, 2019). Nonetheless, pivoting toward analyses focused on latent variables should substantially advance biomarker development and utility.…”
Section: Toward Improving Theta Quantificationmentioning
confidence: 99%
“…This heterogeneity may account for the modest superiority of antidepressant medication over placebo (Cohen’s d ~ 0.3) 2 - 6 . Work over the past two decades has suggested that resting-state electroencephalography (rsEEG) may be able to identify treatment-predictive heterogeneity in depression 7 - 10 . Specific attention has been paid to prefrontal and parietal signals carried by the theta (4-7Hz) and alpha (8-12Hz) frequency bands 7 - 13 .…”
mentioning
confidence: 99%
“…In an additional recent study, machine learning models of EEG profiles and clinical features were predictive of the antidepressant response [72]; however, since the number of participants in some previous EEG studies is relatively small [68,69] and the results are inconsistent, EEG studies must be replicated using large independent samples in the future.…”
Section: Electroencephalographymentioning
confidence: 99%